2021
DOI: 10.15282/ijame.18.1.2021.08.0643
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Clicking-type Noise and Vibration in Automotive HVAC System

Abstract: In this study, the characteristics of clicking-type noise and vibration occurring in the automotive heating, ventilation and air conditional (HVAC) systems are investigated. A lab-scale model of HVAC system is developed, and validation is carried out with a vehicle system. A fixed blower speed of 1 (at an airflow of 2.53 m/s) with alternated air conditional (AC) was implied in this study. Three different sensors namely as tachometer, accelerometer, and microphone were used to measure and prove the existing noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…From the figures, it can be observed that both AC pipe and compressor have the significant peaks of natural frequencies between 50-250 Hz, whereby the highest peak occurred at 148 Hz and 85 Hz for AC pipe and compressor, respectively. This frequency range is corresponded to the region of humming noise and vibration determined by (Satar et al, 2019;2021b). This subsequently will create a resonance to the AC pipe and neighbouring HVAC components while increasing the engine speed during the operation condition.…”
Section: Ema Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…From the figures, it can be observed that both AC pipe and compressor have the significant peaks of natural frequencies between 50-250 Hz, whereby the highest peak occurred at 148 Hz and 85 Hz for AC pipe and compressor, respectively. This frequency range is corresponded to the region of humming noise and vibration determined by (Satar et al, 2019;2021b). This subsequently will create a resonance to the AC pipe and neighbouring HVAC components while increasing the engine speed during the operation condition.…”
Section: Ema Resultsmentioning
confidence: 97%
“…When the compressor is engaged, the HVAC is running smoothly and reduces the overall system vibration. This also supported by the flow of refrigerant fluids which results in an increment of the mass and stiffness of the affected HVAC components (Satar et al, 2021b).…”
Section: Humming Noise and Vibrationmentioning
confidence: 89%
“…The method has been applied in complex air conditional (AC) assemblies. In the experimental approach, it is common to use a microphone to record the sound from vibrating component and compare it with the noise of the models (Wiart et (Satar et al, 2018) were used to correlate the data from the microphone. However, studies involved sound diagnosis are still limited in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Another noise that originated from the HVAC system is a knocking noise. It is generated when the mounting bolts of any HVAC components system were loosened (Satar et al, 2018). Based on the study by Sharma et al (2012), knocking can lead to noise accompanied by a thermostat malfunction and this also related to the humming noise characteristics in the study that has been conducted on the vehicle system by Satar et al (2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation